2019
DOI: 10.1007/978-3-030-28151-9_18
|View full text |Cite
|
Sign up to set email alerts
|

The Anaphase Promoting Complex/Cyclosome (APC/C): A Versatile E3 Ubiquitin Ligase

Abstract: Amyloid beta (Aβ), Adenovirus (Ad), Alzheimer's Disease (AD), Adriamycin (ADM), Acute Myeloid Leukemia (AML), Anaphase Promoting Complex/Cyclosome (APC/C), Adult T-cell leukaemia/lymphoma (ATL), Adenosine Triphosphate (ATP), Ataxia telangiectasia and Rad3-related protein (ATR), BRCA1-associated RING domain protein 1 (Bard1), Brain-Specific Kinase 2 (BRSK2), Budding uninhibited by benzimidazoles 1 (Bub1), Budding uninhibited by benzimidazoles 3 (Bub3), Budding uninhibited by benzimidazoles related 1 (BubR1), Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 393 publications
(424 reference statements)
0
3
0
Order By: Relevance
“…CDC20 plays a pivotal role in the regulation of chromosome segregation and mitotic exit. It exhibits dual, antagonistic functions in the SAC: it functions as an APC/C cofactor and activator (APC/C CDC20 ), but also as a core inhibitor of the APC/C in response to improper kinetochore-microtubule attachments ( Alfieri et al, 2016 ; Yamaguchi et al, 2016 ; Curtis and Bolanos-Garcia, 2019 ; Watson et al, 2019 ). For the latter role, CDC20 associates with BUBR1, MAD2 and BUB3, to form the Mitotic Checkpoint Complex, MCC, (CDC20 MCC ).…”
Section: Resultsmentioning
confidence: 99%
“…CDC20 plays a pivotal role in the regulation of chromosome segregation and mitotic exit. It exhibits dual, antagonistic functions in the SAC: it functions as an APC/C cofactor and activator (APC/C CDC20 ), but also as a core inhibitor of the APC/C in response to improper kinetochore-microtubule attachments ( Alfieri et al, 2016 ; Yamaguchi et al, 2016 ; Curtis and Bolanos-Garcia, 2019 ; Watson et al, 2019 ). For the latter role, CDC20 associates with BUBR1, MAD2 and BUB3, to form the Mitotic Checkpoint Complex, MCC, (CDC20 MCC ).…”
Section: Resultsmentioning
confidence: 99%
“…This process is driven by increasing cyclin-dependent kinase (CDK) activity that needs to be reversed to allow mitotic exit. CDK activity is regulated by the Anaphase Promoting Complex (APC), an E3 ubiquitin ligase that targets cyclins for degradation and activates phosphatases such as Cdc14 to reverse CDK phosphorylation ( Peters, 2006 ; Curtis and Bolanos-Garcia, 2019 ; Lara-Gonzalez et al, 2021 ). While the roles of kinase and opposing phosphatase activities in mitotic progression are well understood, the contribution of other regulatory mechanisms such as translational control is less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…We then identified how DNA-PKcs regulates the ubiquitination and degradation of SIK2. The ubiquitin ligase APC/Cdc20 complex is involved in split sister chromosome segregation and spindle depolymerization, 5 which may be related to DNA-PKcs-mediated degradation and ubiquitination of SIK2. The Co-IP assay results revealed that DNA-PKcs and SIK2 interact with Cdc20 ( Fig.…”
mentioning
confidence: 99%